Institutions, shared guilt, and moral transgression - Dominik Rothenhäusler; Nikolaus Schweizer; Nora Szech (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
We study how institutional design influences moral transgression. People are heterogeneous in their feelings of guilt and can share guilt with others. Institutions determine the number of supporters necessary for immoral outcomes to occur. With more supporters required, every supporter can share guilt more easily. This facilitates becoming a supporter. Conversely, an institution requiring more supporters must rely on people who have higher individual moral standards. We analyze individual thresholds for agreeing to a transgression, depending on the available options for sharing guilt by institutional design. On the aggregate level, we study how institutions affect the likelihood of immoral outcomes. – – Diese Arbeit untersucht den Einfluss von institutionellem Design auf moralische Übertretungen. Menschen unterscheiden sich im Ausmaß ihrer Schuldgefühle und können diese in einer Gruppe mit anderen teilen. Von den jeweiligen Institutionen hängt es ab, wie viel unterstützende Personen für unmoralisches Verhalten notwendig sind. Je mehr dies sind, desto leichter kann jede von ihnen Schuld auf andere abgeben. Dies wiederum erleichtert es, zum Unterstützer für Übertretungen zu werden. Umgekehrt muss eine Institution, für die mehr Unterstützer nötig sind, auf Personen vertrauen, die höhere individuelle moralische Standards haben. Wir analysieren individuelle Hemmschwellen für die Zustimmung zu Übertretungen in Abhängigkeit von den zur Verfügung stehenden Optionen, Schuld über das jeweilige institutionelle Design auf andere zu verteilen. Auf aggregierter Ebene studieren wir, wie Institutionen die Wahrscheinlichkeit von unmoralischem Verhalten beeinflussen.
Keywords: D01; D03; D23; D63; D63; D82; 330; Moral Decision Making; Shared Guilt; Group Absolution; Diffused Responsibility; Institutional Design; Committee Decisions; Moral Transgression